PSI-36 Taxonomic and functional assessment reveals specific rumen microbial species and gene families associated with feed efficiency in Angus cattle. (7th December 2018) - Neves, A; Lê Cao, K; Mandal, S; Sharpton, T; McAllister, T; Guan, L
Abstract: A greater understanding of the rumen microbiota and its function may lead to improved feed efficiency in cattle. The objectives of this study were: (i) to characterize bacterial phylotypes and microbial functions in the rumen of two breeds of beef cattle fed forage-based diets and (ii) to identify specific taxonomic microbial groups and gene families associated with feed conversion rate (FCR). Total RNA was extracted from twenty-four rumen content samples collected over four-time points (0, 80, 100, 180 d) from six purebred bulls (Black Angus= 3; Red Angus= 3) and sequenced (RNA-seq). Microbial classification and functional characterization of genes were analyzed using Kraken and ShotMAP, respectively. Sparse partial least square (sPLS-DA) multivariate regression models were used to identify a panel of bacterial species and microbial gene families (microbial signatures) that discriminate and characterize the different breeds. An Analysis of Composition of Microbiomes (ANCOM) was used to detect differentially abundant microbes and functions when FCR was adjusted to time. Bacteroidetes, Firmicutes, Proteobacteria, Spirochaetes, Verrucomicrobia, Tenericutes, and Fibrobacteres phyla accounted for 97% of the bacterial population in all bulls. Gene families were mostly enriched from ribosome, Calvin cycle, gluconeogenesis, glycolysis, and citrate cycle modules identified in the KEGG database. sPLS-DA detected 25 bacterial species and 10 gene families discriminating the two breeds. Specifically, bacterial taxa including Chitinophaga pinensis, Clostridium stercorarium, Ruminoccocus albus, and functions including large and small subunits ribosomal proteins L16 (K02878) and S7 (K02992) and NADH-quinone oxidoreductase subunit F exhibited a higher abundance in Black Angus as compared to Red Angus. Moreover, it was found that the abundances of Ruminoccocus albus and large and small subunits ribosomal proteins L16 were influenced by FCR and time across breeds, underlining the important role of bacterial composition and microbial functions associated with the catalysis of mRNA-directed protein synthesis in forage fed beef bulls.